Answer: 16x^2 - 9x + 11
Step-by-step explanation:
(5x^2+8x+18)+(11x^2-17x-7)
5x^2+8x+18+11x^2-17x-7
16x^2 - 9x + 11
Answer:
252p
Step-by-step explanation:
Answer:
Step-by-step explanation: v> -2 the > has a line under it
Answer:
37.6%
Step-by-step explanation:
P(A|B) = P(A and B) / P(B)
P(red | car) = P(red and car) / P(car)
P(red | car) = 0.32 / 0.85
P(red | car) = 0.376
Answer: 14x^2 - 84x - 7
====================================================
Explanation:
The like terms 6x^2 and 8x^2 combine to 14x^2
The like terms -8x and -76x combine to -84x
Nothing pairs with the -7, so its stays as is.
Standard form is where we list the terms in decreasing exponent order. We can think of -84x as -84x^1 and the -7 as -7x^0. So 14x^2 - 84x - 7 would be the same as 14x^2 - 84x^1 - 7x^0. The exponents count down: 2,1,0.
The final answer is a trinomial since it has three terms. It is also a quadratic because the degree (highest exponent) is 2.